2012
DOI: 10.1038/cgt.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of tumor growth by needle-free jet injection of anti-C7orf24 siRNA

Abstract: Chromosome 7 open reading frame 24 (C7orf24), which was identified by proteome analysis, is upregulated in various types of cancer and is associated with cellular proliferation. However, in vivo antitumor effect by knockdown of C7orf24 has not been clarified. In this study, we investigated that the antitumor effect of anti-C7orf24 small interfering RNA (siRNA) administered by needle-free jet injection (JI) on lung cancer-bearing mice. Transfection of anti-C7orf24 siRNA induced cytotoxicity in cultured human lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
(25 reference statements)
0
28
0
Order By: Relevance
“…Knockdown of GGCT by siRNA resulted in cells with slower cell growth rates, increased clustering, and reduced invasiveness and motility as measured by standard in vitro methods, consistent with GGCT being involved in tumor progression (Uejima et al, 2011). Similarly, reduction of GGCT levels by siRNA inhibited the growth of human lung squamous cell carcinoma in a mouse model (Hama et al, 2012). GGCT is an effective diagnostic marker in esophageal squamous cell carcinoma, where higher levels of expression correlate with a more aggressive phenotype (Takemura et al, 2014).…”
Section: Glutathione Salvagementioning
confidence: 99%
“…Knockdown of GGCT by siRNA resulted in cells with slower cell growth rates, increased clustering, and reduced invasiveness and motility as measured by standard in vitro methods, consistent with GGCT being involved in tumor progression (Uejima et al, 2011). Similarly, reduction of GGCT levels by siRNA inhibited the growth of human lung squamous cell carcinoma in a mouse model (Hama et al, 2012). GGCT is an effective diagnostic marker in esophageal squamous cell carcinoma, where higher levels of expression correlate with a more aggressive phenotype (Takemura et al, 2014).…”
Section: Glutathione Salvagementioning
confidence: 99%
“…The gene‐silencing efficacy of G‐PEG–HA–NP was evaluated by detecting GGCT expression level by Western blot measurement after transfection. The sequence of siRNA used in this study has shown efficient gene silencing of C7orf24 in other cell lines, such as A549 cells and EBC‐1 cells . After transfection with anti‐GGCT siRNA‐loaded lipofectamine RNAiMAX or PEG–HA–NP, the GGCT expression level was significantly decreased (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…And Hama et al developed a needle-free jet injection for anti-C7orf24 siRNA which was injected to subcutaneous EBC-1 tumors in mice. The treatment significantly reduced the C7orf24 protein levels in the tumor tissue as assessed by immunohistochemistry (IHC), and additionally caused cytotoxicity in the tumors as shown by cell apoptosis/necrosis measured via flow cytometry [40]. …”
Section: Nucleic Acid Modificationsmentioning
confidence: 99%
“…While Das et al force-fed balb/c mice with BaP and SA to provoke the development of lung cancer [115], others have used a Kras LA1 model to mimic human NSCLC [101-103]. Besides these two models that seem more translationally relevant, most publications describe the use of xenograft models where for example A549 NSCLC cells [35, 48, 75, 114, 120, 129], H460 cells [105, 127, 131, 132], H2009 cells [107], EBC-1 cells [40], H358 cells [48] or H292 cells [76] are injected s.c. Alternatives are the injection of A549 cells in matrigel into the dorsal side of ribcage for an orthotopic model [131, 132] or the intratracheal administration of A549 [80, 137, 138] or LA-4 mouse tumor cells [134] to the lung, which mimics the clinical reality of lung cancer better than xenograft models.…”
Section: Disease Modelsmentioning
confidence: 99%